Blood microRNA Signatures Serve as Potential Diagnostic Biomarkers for Hepatic Sinusoidal Obstruction Syndrome Caused by Gynura japonica Containing Pyrrolizidine Alkaloids - Wang, Xunjiang; Zhang, Wei; Yang, Yongfeng; Chen, Yiran; Zhuge, Yuzheng; Xiong, Aizhen; Yang, Li; Wang, Zhengtao (Frontiers in Pharmacology, 2021)
Background & Aims: The Gynura japonica-induced hepatic sinusoidal obstruction syndrome (HSOS) is closely related to pyrrolizidine alkaloids (PAs), and its prevalence is increasing worldwide in recent years. However, no effective therapy for PA-induced HSOS in clinics is available partially due to the failure of quick diagnosis. This study aims to identify blood microRNA (miRNA) signatures as potential biomarkers for PA-induced HSOS in clinics. Methods: The microarray-based miRNA profiling was performed on blood samples of the discovery cohort, which consisted of 9 patients with HSOS and 9 healthy donors. Differentially expressed miRNAs were further confirmed using a validation cohort, which consisted of 20 independent patients with HSOS. In addition, the rat model was established through the oral administration of the total alkaloid extract from G. japonica to investigate the association of miRNA biomarkers with the progression of HSOS. Bioinformatic analyses, including GO and KEGG enrichment, receiver operating characteristics curve, and correlation analyses, were conducted to evaluate the accuracy of the potential miRNA biomarkers. Results: Three miRNAs, namely, miR-148a-3p, miR-362-5p, and miR-194-5p, were overexpressed in patients and rats with PA-induced HSOS. These miRNAs were positively related to the severity of liver injury and displayed considerable diagnostic accuracy for patients with HSOS with areas under the curve over 0.87. Conclusions: In summary, this study demonstrated that three miRNAs, i.e., hsa-miR-148a-3p, hsa-miR-362-5p, and hsa-miR-194-5p, might serve as potential biomarkers for PA-induced HSOS in clinics.